Type specimens matter: new insights on the systematics, taxonomy and nomenclature of the subalpine warbler (Sylvia cantillans) complex. Issue 1 (17th January 2020) - Zuccon, Dario; Pons, Jean-Marc; Boano, Giovanni; Chiozzi, Giorgio; Gamauf, Anita; Mengoni, Chiara; Nespoli, Davide; Olioso, Georges; Pavia, Marco; Pellegrino, Irene; Raković, Marko; Randi, Ettore; et al.
Abstract: We revise the taxonomy of the Sylvia cantillans complex, a group of phenotypically distinct warblers with mainly parapatric distributions around a large part of the Mediterranean basin. We redefine the species limits using a combination of mitochondrial and nuclear markers and we objectively link available names to the genetically defined lineages by genotyping the surviving type specimens. In addition, the study of archival documents clarifies the exact composition of type series and provides further evidence for the identification of lost types. These results support the recognition of three species-level taxa: Moltoni's warbler, Sylvia subalpina (north-central Italy, Corsica, Sardinia and the Balearics); the western subalpine warbler, S. iberiae (North Africa, Iberia, southern France and extreme north-west Italy); and the eastern subalpine warbler, S. cantillans, with subspecies S. cantillans cantillans (southern Italy, Sicily) and S. cantillans albistriata (Balkans, Greece, western Turkey).